Photodynamic inactivation of a RNA-virus model using water-soluble β-octa-Substituted pyridinium-pyrazolyl phthalocyanines - Gamelas, Sara R. D. (2023)
Among the various groups of microorganisms, viruses have generally a greater capacity for mutation, especially RNA viruses, as was demonstrated by SARS-CoV2 virus mutations. This high mutation rate promotes the development of their resistance to traditional antivirals and establishes the resistance behaviour in virus populations, decreasing their susceptibility to these drugs. In this context, the photodynamic treatment appears as a potentially effective method against microorganisms and, considering its mode of action is not likely to lead to the development of resistance. In this work, two newly zinc(II) phthalocyanines (ZnPcs) bearing pyridinium-pyrazolyl groups (2a and 3a) were synthesized, characterized, and applied in photodynamic inactivation (PDI) of bacteriophage Φ6 (or Phage Phi6) as a RNA-virus model. These quaternized dyes were applied at different concentrations (from 5.0 to 20 μM, and under white light irradiation in the irradiance range between 50 and 150 mW/cm2) to test their efficiency for possible clinical or environmental applications. The results showed that the new cationic ZnPcs 2a and 3a efficiently inactivate the RNA-virus model (bacteriophage Φ6), even at the lowest tested irradiance. These compounds are thus promising photosensitizers to be used in various contexts.